STRATEGI PENINGKATAN INVESTASI KABUPATEN INDRAMAYU - -, Komadin; Hartoyo, Sri; Hakim, Dedi Budiman (Jurnal Manajemen Pembangunan Daerah, 2013)
Indramayu is regency that produce Oil and Earth Gas in Indonesian and as main paddy granary for West Java Province. So that the investment in this sectors is a strategic effort. Region development study have intention to know investment developing, analyzing investment competitiveness and make Indramayu Regency investment increasing strategy. Methods that is used in this study is competitiveness analysis by using SWOT (Strength, Weakness, Opportunity and Threats) and AHP (Analytical Hierarchy Process) method. The Analysis showing result: First, Indramayu Regency up to year 2000-2005 experience investment decreases. Second, analysis result about investment competitiveness show the priorities factor that most regard Indramayu Regency investment competitiveness alternately which ares strength factor (0,458), weakness (0,280), opportunity (0,162), and threat (0,100). Third, from the competitiveness analysis, priority alternative strategy in increasing Indramayu Regency investment alternately which are developing zone and industrial cluster (0,551), developing agroindustry upstream until downstream (0,237), developing institution (0,138), and increasing human capital quality (0,074).Keywords: Indramayu, Competitiveness, Investment Increasing Strategy